Peran Guru Agama Dalam Mengembangkan Emosional Dan Spiritual Siswa Di SMP PGRI 2 Driyorejo - Akhmad Rofik; Ashari Ashari; Rudolf Crysoekamtoe (Jurnal Budi Pekerti Agama Islam, 2024)
The results of the study are known that the Role of Islamic Religious Teachers in developing emotional and spiritual intelligence in Driyorejo PGRI 2 Junior High School namely (1) the teacher acts as a motivator, advisor, role model, guide, disciplinarian, corrector, demonstrator, guide for students in developing emotional intelligence and spiritual at SMP PGRI 2 Driyorejo; (2) Supporting factors in developing emotional and spiritual intelligence are good communication between students and teachers and the presence of infrastructure. While the obstacles are the lack of students' ability to understand and apply existing learning in school; (3) The implication is that students can recognize the emotions that exist in themselves and others, and be able to motivate themselves and others.